+0  
 
+1
39
5
avatar+181 

1

2      

                   

3

4

 

Thanks so much!

Johnnyboy  Sep 5, 2018
 #1
avatar+88871 
+1

x + 5y  = -15

y  = (1/5) x + 1        sub the second into the first for y  and we have

 

x + 5 ( 1/5 x + 1)  = -15

x + x + 5  = -15

2x + 5  = -15     subtract 5 from  both sides

2x  = -20     divide both sides by 2

x  = -10

 

And using    y  = (1/5)x + 1  to find  x, we have   y  =(1/5) (-10) + 1  = -2 + 1   =  -1

 

So   (x , y)   = ( -10 , -1)

 

 

cool cool cool

CPhill  Sep 5, 2018
edited by CPhill  Sep 5, 2018
 #2
avatar+88871 
+1

x + y  = 6

x  =  y + 4        sub the second into the first for  x

 

(y + 4) + y  = 6

2y + 4  = 6

2y  = 2

y = 1

 

And   x   =  y + 4  =  1 + 4   = 5

 

So   (x, y)  = ( 5 , 1)

 

 

cool cool cool

CPhill  Sep 5, 2018
 #3
avatar+88871 
+1

2x - 3y  = -27     multiply through by 3   ⇒   6x - 9y = -81    (1)

-3x + 2y  = 23   multiply through  by  2 ⇒   -6x + 4y  =  46    (2)

 

Add (1)  and (2)  and we get

 

-5y  = -35     divide both sides by  -5

y  = 7

 

And  using   2x  -  3y = -27  to  find x we get

 

2x - 3(7)  = -27

2x - 21  = -27     add 21 to  both sides

2x = -6    divide both sids by  2

x  = -3

 

So  (x ,y )  =  ( -3, 7)

 

 

cool cool cool

CPhill  Sep 5, 2018
 #4
avatar+181 
+1

Thanks man :D

Johnnyboy  Sep 5, 2018
 #5
avatar+88871 
+1

Last one

 

x + 3y - z  = 6    

4x - 2y + 2z = -10    

6x + z  = -12

 

Sorry..Johnny...but I gotta' go in just a minute

 

The answer to  this is   (x ,y , z)   = ( -3, 5, 6)

 

When I get back on...I'll give you a complete run through...if you need it  !!!

 

 

cool cool cool

CPhill  Sep 5, 2018

6 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.